Monitoring indicators of scholarly language: A progress monitoring tool for documenting changes in narrative complexity over time - Israelsen-Augenstein, Megan; Fox, Carly; Gillam, Sandra L.; Holbrook, Sarai; Gillam, Ronald (Frontiers in Education, 2022)
The purpose of this cross-sectional study was to determine the differences in narrative macrostructure abilities of children in different age groups using a progress monitoring tool based in discourse theory. A majority of existing research regarding narrative developmental patterns has been based in schema theory. The Monitoring Indicators of Scholarly Language (MISL) rubric is based in discourse theory and was designed to characterize aspects of narrative proficiency in school-age children. The data for this project consisted of 687 narratives elicited using the Aliens subtest from The Test of Narrative Language—Second Edition (TNL-2). There were 1,597 participants who ranged in age from 4; 0 to 15; 0 (year; month). An ordinary least squares regression where age predicted total macrostructure score, followed by a series of post hoc ordinal logistic regressions (OLR) where age predicted each individual MISL rubric element was used. Results of both the simple regression on total macrostructure score and the series of ordinal regression analyses for each macrostructure element indicated that age was a significant predictor of the scores children received. Collectively, these results suggest that the MISL is a developmentally valid measure of narrative production abilities. Developmental milestones based on discourse theory are reported to be substantially later than has been reported for schema theory. The differences are highlighted and the implications for progress monitoring for narrative development are discussed.